Support and Its Effect for Persons Affected by COPD and Their Next of Kin - an Systematic Integrative Review - Johansson H; Jonasson LL; Berterö C (International Journal of COPD, 2025)
Helena Johansson,1,2,* Lise-Lotte Jonasson,3,* Carina Berterö1,* 1Division of Nursing Sciences and Reproductive Health, Department of Health, Medicine and Caring Sciences, Linköping University, Linköping, Sweden; 2Department of Medical Specialist in Motala, and Department of Health, Medicine and Caring Sciences, Linköping University, Linköping, Sweden; 3Department of Nursing, School of Health and Welfare, Jönköping University, Jönköping, Sweden*These authors contributed equally to this workCorrespondence: Helena Johansson, Email Helena.Johansson@liu.seIntroduction: Chronic Obstructive Pulmonary Disease (COPD) is an irreversible lung disease. People with COPD and their next of kin are affected in daily life and need support from each other, health care, and the surrounding society.Objective: This systematic integrative review aims to identify which support is given to persons affected by COPD and/or their next of kin from the health care and surrounding society. A second aim was to evaluate the support.Methods: A systematic integrative review was conducted to aggregate the knowledge by searching PubMed, CINAHL, PsycINFO, Scopus, and Web of Science databases. Search terms were chronic obstructive pulmonary disease (COPD) and support. The time limit was 2014– 2023. The review protocol was registered on PROSPERO (CRD42023462784). The inclusion was selected from the aim, and quality review instruments checked quality. The result was analyzed with a constant comparison method.Results: Persons with COPD receive support from their next of kin, practically and emotionally. Health care also supplies support through information, knowledge, and different training programs. Health care can be in all types of health care, from hospital and primary care to care in the home, all with varying types of support. The next of kin supplies support to their sick relative, becomes support from health care on a small scale, and wishes for more information, knowledge, and understanding about the disease, symptoms, and treatment. The sick person and their carer want to be acknowledged and supported more on their terms.Conclusion: Support for next of kin is virtually non-existent. Next of kin needs more support from health care and the surrounding society. Healthcare interventions in the future need to involve the person with COPD and the next of kin in a person-centered approach out of every person´s needs and support more on their terms.Keywords: chronic obstructive pulmonary disease, COPD, next of kin, support, person centered care, integrative review